2020
DOI: 10.1002/ps.6035
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of rapamycin on Botryosphaeria dothidea and its effect against Chinese hickory canker

Abstract: BACKGROUND: The trunk canker caused by Botryosphaeria dothidea is a devastating disease for Chinese hickory (Carya cathayensis) in China. Chemical fungicides are commonly and repeatedly applied to control the disease; however, fungicide application raises major environmental and food safety issues. Ecofriendly biocontrol alternatives were urgently needed. Herein, the antifungal activity of a natural secondary metabolite, rapamycin, against B. dothidea and the effect of a rapamycin-producing Streptomyces hygros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…47,48 It was reported that the primary microorganism responsible for the production of antibiotics is Streptomyces. 49 The Streptomyces species was widely used for the production of some antibiotics such as rapamycin 50 and avermectin, 51 and both of them were effective in controlling pests and diseases in agricultural crops. Act-X 2 , Act D, and Act-X O⊎ were the three main compounds isolated from the EAE of Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 It was reported that the primary microorganism responsible for the production of antibiotics is Streptomyces. 49 The Streptomyces species was widely used for the production of some antibiotics such as rapamycin 50 and avermectin, 51 and both of them were effective in controlling pests and diseases in agricultural crops. Act-X 2 , Act D, and Act-X O⊎ were the three main compounds isolated from the EAE of Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…The primary method of controlling this disease still involves chemicals, which entails risk when they are used improperly. Hence, it is crucial to embrace novel and 27 curcumin, 28 rapamycin, 29 and natamycin. 30 Honokiol, a plantderived antimicrobial substance, has promising applications in agriculture, fishery, medicine, and related fields.…”
Section: Discussionmentioning
confidence: 99%
“…So far, several extracts from plants or microorganisms have been discovered to exhibit a potent inhibitory effect on B. dothidea . Examples include carvacrol, 27 curcumin, 28 rapamycin, 29 and natamycin 30 . Honokiol, a plant‐derived antimicrobial substance, has promising applications in agriculture, fishery, medicine, and related fields.…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin is a macrolide that is originally developed as an antifungal agent ( Jiang et al, 2021 ). Rapamycin is useful in the treatment of various cancers due to its inhibitory effect on the PI3K/AKT/mTOR pathway ( Alzahrani, 2019 ).…”
Section: Discussionmentioning
confidence: 99%